Novel Terthiophene-Substituted Fullerene Derivatives as Easily Accessible Acceptor Molecules for Bulk-Heterojunction Polymer Solar Cells. (10th July 2014) - Nisic, Filippo; Colombo, Alessia; Dragonetti, Claudia; Cominetti, Alessandra; Pellegrino, Andrea; Perin, Nicola; Po, Riccardo; Tacca, Alessandra
Abstract : Five fulleropyrrolidines and methanofullerenes, bearing one or two terthiophene moieties, have been prepared in a convenient way and well characterized. These novel fullerene derivatives are characterized by good solubility and by better harvesting of the solar radiation with respect to traditional PCBM. In addition, they have a relatively high LUMO level and a low band gap that can be easily tuned by an adequate design of the link between the fullerene and the terthiophene. Preliminary results show that they are potential acceptors for the creation of efficient bulk-heterojunction solar cells based on donor polymers containing thiophene units.